2021
DOI: 10.1111/nep.13876
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of Chinese patients with B‐cell lymphoproliferative disorders and kidney infiltration

Abstract: AimDirect kidney involvement in B‐cell lymphoproliferative disease is a rare disorder with only a few studies reported in Caucasian patients. The clinicopathological characteristics and outcome of this entity remain poorly described.MethodsWe retrospectively studied all adult Chinese patients who had histology‐proven renal parenchymal infiltration by malignant B‐cells between 1 January 2000 and 31 December 2018 at two tertiary hospitals in Hong Kong. Clinical, pathological and radiological data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…While cholecystitis isn't an uncommon presenting symptom for GI involvement of lymphoma, it is rare for MCL to be the underlying lymphoma subtype [7]. Additionally, renal lymphomatous involvement presenting as nephromegaly is rare in all subtypes of lymphoma, including MCL [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While cholecystitis isn't an uncommon presenting symptom for GI involvement of lymphoma, it is rare for MCL to be the underlying lymphoma subtype [7]. Additionally, renal lymphomatous involvement presenting as nephromegaly is rare in all subtypes of lymphoma, including MCL [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to gallbladder involvement of lymphoma, direct kidney involvement of lymphoma is extremely rare. A retrospective review over an 18-year time period at two tertiary hospitals identified 20 total cases of patients with renal parenchymal infiltration of lymphoma [8]. Of the 20 cases identified, only one was found to be MCL, with diffuse large B-cell lymphoma, follicular lymphoma, and marginal zone lymphoma being more commonly associated with parenchymal involvement of the kidneys [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations